Catheter related blood stream infections in ICU: A study from North India - Gahlot, Rupam; Nigam, Chaitanya; Kumar, Vikas; Gupta, Munesh (International Journal of Infection Control, 2013)
Introduction: Central venous catheter (CVC) insertion is common in ICU practices; this can be a source of dangerous bacteremia, sepsis, multi organ failure and sometimes even death. Aim: We conducted this study to find out rate of Catheter colonization, Catheter related blood stream infections (CRBSI), their association and microbial spectrum of CRBSI in critical care unit over 1 year period. Material and methods: Patients admitted in critical care units requiring central venous catheterization and presenting with signs of septicemia during catheterization period were investigated for catheter related blood stream infections. Tip of Central venous catheter (CVC) as well as peripheral blood for culture were obtained simultaneously and processed according to pre determined protocol. Antimicrobial susceptibility testing was done for the isolated organisms. Results: CRBSI rate 10 per thousand catheter days with Staphylococcus sp. as most common organism was observed. Conclusion: Since central venous catheters are increasingly being used in the critical care, regular surveillance for infection associated with them is essential.